2011
DOI: 10.1111/j.1365-2672.2011.05173.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and bioactive potential of endospore-forming bacteria cultured from the marine sponge Haliclona simulans

Abstract: Aims:  Despite the frequent isolation of endospore‐formers from marine sponges, little is known about the diversity and characterization of individual isolates. The main aims of this study were to isolate and characterize the spore‐forming bacteria from the marine sponge Haliclona simulans and to examine their potential as a source for bioactive compounds. Methods and Results:  A bank of presumptive aerobic spore‐forming bacteria was isolated from the marine sponge H. simulans. These represented c. 1% of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 54 publications
2
24
0
2
Order By: Relevance
“…Phelan et al . [11] reported that a bank of aerobic spore-forming bacteria was isolated from the marine sponge Haliclona simulans , belonging to the class of Demospongiae. A large diversity of endospore-forming bacteria was distributed through a variety of Bacillus species, including ubiquitous species, such as B. subtilis, B. pumilus (found by us in I. muscarum ), B. licheniformis and B. cereus group, as well as species that are typically associated with marine habitats, such as B. hwajinpoensis (found by us in I. muscarum and in G. cydonium ), B. aquimaris, B. algicola, B. baekryungensis (found by us in I. muscarum ).…”
Section: Resultsmentioning
confidence: 99%
“…Phelan et al . [11] reported that a bank of aerobic spore-forming bacteria was isolated from the marine sponge Haliclona simulans , belonging to the class of Demospongiae. A large diversity of endospore-forming bacteria was distributed through a variety of Bacillus species, including ubiquitous species, such as B. subtilis, B. pumilus (found by us in I. muscarum ), B. licheniformis and B. cereus group, as well as species that are typically associated with marine habitats, such as B. hwajinpoensis (found by us in I. muscarum and in G. cydonium ), B. aquimaris, B. algicola, B. baekryungensis (found by us in I. muscarum ).…”
Section: Resultsmentioning
confidence: 99%
“…Comparisons between culturable bacterial communities from marine sponges are difficult to address since differences in media and culture conditions can significantly influence the isolation and cultivability of distinct bacterial isolates (Sipkema et al, 2011). In spite of this, it seems that some genera are commonly found among marine sponges, such as Pseudovibrio (Enticknap et al, 2006; Mohamed et al, 2008; Menezes et al, 2010; Santos et al, 2010; Flemer et al, 2011; Bruck, Reed & McCarthy, 2012; Margassery et al, 2012), Bacillus (Hentschel et al, 2001; Webster et al, 2001; Pabel et al, 2003; Lafi, Garson & Fuerst, 2005; Zhu, Li & Wang, 2008; Bruck et al, 2010; Devi et al, 2010; Santos et al, 2010; Flemer et al, 2011; Phelan et al, 2011; Bruck, Reed & McCarthy, 2012; Margassery et al, 2012), and Ruegeria (Mohamed et al, 2008; Menezes et al, 2010; Bruck, Reed & McCarthy, 2012; Margassery et al, 2012; Esteves et al, 2013; Haber & Ilan, 2013). Such bacterial genera can be found in distinct marine sponge species collected at distant geographic areas and with low phylogenetic relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Paenibacillus isolates belong to the microbial community of sponges, although they are found less abundantly than Bacillus (Phelan et al, 2011). The physiological role of sporeformers within sponge tissues is still unknown (Phelan et al, 2011), but probiotic activity was verified in Bacillus cereus and Paenibacillus sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these microbes are proven to produce medically relevant compounds including ecteinascidin-743 (Yondelis ® ), dolastatin-10 (Adcetris ® ) and halichondrin B (Halaven ® ) [12]. As a result, marine sponge-associated microbes are sought after for natural product discovery [13,14,15,16] due to their potential for delivering novel bioactive compounds [17,18]. In general, the large scale production of microbial-derived secondary metabolites for study and use is hampered by the lack of these bacteria in culture collections, either through an inability to culture them or identify the microbes responsible for producing an observed bioactivity [19].…”
Section: Introductionmentioning
confidence: 99%